Large scale structure-function mappings of the human subcortex. Issue 1 (December 2018) - Keuken, Max; Maanen, Leendert; Boswijk, Michiel; Forstmann, Birte; Steyvers, Mark
Abstract Currently little is known about structure-function mappings in the human subcortex. Here we present a large-scale automated meta-analysis on the literature to understand the structure-function mapping in the human subcortex. The results provide converging evidence into unique large scale structure-function mappings of the human subcortex based on their functional and anatomical similarity.